Pengaruh Viral Marketing, Online Customer Review, Online Customer Rating, Dan Kemudahan Penggunaan Terhadap Keputusan Pembelian Pada Social Commerce Tiktok Shop (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Taufiq Hidayat; Mohammad Rizal; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract In the current era of globalization, the internet is a very important need for everyone. In the era of rapidly developing information technology development, e-commerce has become part of business dynamics, the difference between e-commerce and social commerce lies in business goals, relationships between consumers, and interaction systems. At present there are many social commerce that are used by people in Indonesia, one of which is the TikTok Shop. TikTok and TikTok Shop are combined into one application, in which TikTok Shop is a business platform published by TikTok to make it easy for users who want to buy or sell a product. The purpose of this study was to determine and analyze the effect of Viral marketing, Online customer reviews, Online customer ratings and ease of use simultaneously on purchasing decisions at social commerce TikTok Shop. The population in the study were active students at the Islamic University of Malang who had purchased at the TikTok Shop. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 95 respondents and using the SPSS analysis tool. The results showed that partially viral marking, online customer reviews and ease of use had a significant effect on purchasing decisions while online customer ratings did not have a significant effect on purchasing decisions. Simultaneously viral marketing, online customer reviews, online customer ratings, ease of use have a significant effect on purchasing decisions. Keywords : Viral Marketing, Online Customer Reviews, Online Customer Ratings, Ease Of Use, Purchasing Decisions